Mental and social health in disasters: the Sphere standards and post‐tsunami psychosocial interventions in Asia. Issue 3 (17th November 2015) - Henderson, Silja E.K.; Elsass, Peter; Berliner, Peter
Abstract : The primary objective of this paper is to examine and inform the mental health and psychosocial support standards of the 2011 edition of the Sphere Project's Humanitarian Charter and Minimum Standards in Humanitarian Response . This is done through a qualitative analysis of internal evaluation documents, reflecting four long‐term humanitarian psychosocial programmes in different countries in post‐tsunami Asia. The analysis yielded three overall conclusions. First, the Sphere standards on mental health and psychosocial support generally are highly relevant to long‐term psychosocial interventions after disasters such as the Indian Ocean tsunami of 26 December 2004, and their application in such settings may improve the quality of the response. Second, some of the standards in the current Sphere handbook may lack sufficient guidance to ensure the quality of humanitarian response required. Third, the long‐term intervention approach poses specific challenges to programming, a problem that could be addressed by including additional guidance in the publication.